A Surveillance System for Enhancing the Safety of Rescue Teams - Hon, Zdenek; Smrcka, Pavel; Hana, Karel; Kaspar, Jan; Muzik, Jan; Fiala, Radek; Viteznik, Martin; Vesely, Tomas; Kucera, Lukas; Kuttler, Tomas; Kliment, Radim; Navratil, Vaclav (Communications - Scientific letters of the University of Zilina, 2015)
The article summarizes preliminary results of the research and development of a system focused on enhancing the safety of teams participating in the integrated rescue system managing extraordinary events or crisis situations (fire, mass disaster, release of harmful industrial substances), and on the support in the course of training. Individual partial technical solutions are mentioned, which should lead to providing automatized telemetric monitoring equipment in a more resistant form making it possible to recognize the nature and intensity of the motion, including the determination of the topical and total energy outputs, monitoring of environmental parameters (temperature, smoke, etc.) and back analysis of the intervention course or training in real time, and the monitoring of health-physiological parameters and signalling risk conditions (physical exhaustion, stress, overheating, etc.) under extreme measures.